MODERNIZATION OF HIGHER EDUCATION UKRAINE IN THE CONTEXT OF NATIONAL SECURITY - Лузік, Е. В.; Хоменко-Семенова, Л. О. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
This study examines the important issue of realizing Ukraine’s national interests by providing educational security, which is the guarantor of the independence of the state, a condition for its sustainable development and the growth of the well-being of citizens. The conditions for the influence of the era of industrial society are considered, and the classical paradigm of education was formed. Criteria are determined without a pie audit such as: technology, mathematics, computer literacy; Cooperation and international competition in higher education; Foreign languages ​​and global awareness; National identity Particular attention is paid to the issue of modernization of educational policy in the context of Ukraine’s national security